An Islamic Law Between Rights and Obligations in The Study of Islamic Law Philosophy - Hikmah, Ilmiani Nurul (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Rights are possessions, possessions, which are not only objects, but also actions, thoughts and authority. In the Qur'an we find the word al-haqq which is a translation of the word rights which means property or the person who controls it. In theology, right also means power, authority, or authority. Liability is a burden or responsibility that is contractual in nature. In other words, an obligation is something that should be given. With the existence of rights and obligations, justice also arises, namely the recognition and treatment of rights. Meanwhile, in Islamic Law, justice can be interpreted as a term used to indicate equality or being in the middle of two cases or putting something in its place. This research uses qualitative research methods with library research as the data source. As a result, where there are rights there are obligations, and where there are obligations there is justice, namely applying and carrying out rights in accordance with a balanced place, time and level. By implementing rights, obligations and justice, this will automatically support the creation of moral actions. Keywords: Islamic Law, Rights and Obligations, Islamic Law Philosophy